Sex differences between parental pregnancy characteristics and nonalcoholic fatty liver disease in adolescents - Ayonrinde, Oyekoya; Adams, L.; Mori, T.; Beilin, L.; de Klerk, N.; Pennell, C.; White, S.; Olynyk, John (John Wiley & Sons Inc., 2018)
Nonalcoholic fatty liver disease (NAFLD) is a complex chronic liver disorder. Examination of parental pregnancy-related characteristics may provide insights into the origins of risk of NAFLD in offspring. We examined relationships between parental pregnancy-related characteristics and NAFLD in 1,170 adolescent offspring aged 17 years participating in the Western Australian Pregnancy (Raine) Cohort Study. Fatty liver was diagnosed using liver ultrasound. NAFLD was diagnosed in 15.2% of adolescents at age 17 years. In univariate analysis, maternal factors associated with NAFLD in female offspring were younger maternal age (P = 0.02), higher maternal prepregnancy BMI (P < 0.001), higher maternal weight gain by 18 weeks' gestation (P < 0.001), and maternal smoking during pregnancy (P = 0.04). Paternal age or body mass index (BMI) were not associated with NAFLD in female offspring. In contrast, higher paternal BMI (P < 0.001), maternal prepregnancy BMI (P < 0.001), and lower family socioeconomic status (SES) at time of birth (P = 0.001), but not parental age nor maternal gestational weight gain, were associated with NAFLD in male offspring. Using multivariate logistic regression, factors independently associated with NAFLD after adjusting for obesity in adolescent females included maternal obesity (odds ratio [OR], 3.46; 95% confidence interval [CI] , 1.49-8.05; P = 0.004) and maternal weight gain =6.0 kg by the 18th week of gestation (OR, 1.10; 95% CI, 1.04-1.15; P < 0.001). In adolescent males, family SES at the time of birth (OR, 9.07; 95% CI, 1.54-53.29; P = 0.02) remained significantly associated with NAFLD after multivariate modeling adjusted for adolescent obesity. Conclusion: Early-life contributors to NAFLD show considerable sexual dimorphism. Maternal obesity and higher early-mid gestational weight gain were associated with NAFLD in female offspring, whereas lower family SES at birth was associated with NAFLD in male offspring independent of adolescent obesity.